Bimatoprost sustained‐release intracameral implant reduces episcleral venous pressure in dogs. (19th February 2018) - Lee, Susan S.; Burke, James; Shen, Jie; Almazan, Alexandra; Orilla, Werhner; Hughes, Patrick; Zhang, Jane; Li, Huajiang; Struble, Craig; Miller, Paul E.; Robinson, Michael R.
Abstract: Objective: To determine the effect of a bimatoprost sustained‐release intracameral implant (Bimatoprost SR) on episcleral venous pressure (EVP) in normal dogs. Methods: Normotensive beagle dogs were randomized to receive Bimatoprost SR 30 μg ( n = 7) or sham injection (needle insertion only, n = 7) in one eye on day 1. EVP was measured with an episcleral venomanometer through day 65. Episcleral aqueous outflow vessels were identified using fluorescence imaging following intracameral injection of indocyanine green in one additional animal. A separate cohort of dogs that had been trained for conscious intraocular pressure (IOP) measurements received Bimatoprost SR 30 μg ( n = 8) in one eye; IOP was evaluated through day 66. Results: Baseline mean EVP was 10.0 mmHg in the Bimatoprost SR group and 10.4 mmHg in the sham group. Eyes treated with Bimatoprost SR exhibited a transient increase in mean EVP that peaked at day 8, followed by a decrease to levels below baseline. From day 29 to day 65, the change in mean EVP from baseline ranged from −2.4 to −3.9 mmHg ( P < 0.05 vs. sham). Baseline mean IOP in eyes treated with Bimatoprost SR was 14.9 mmHg, and a steady IOP reduction was maintained through day 66. Bimatoprost SR‐treated eyes exhibited a selective, sustained dilation of aqueous outflow vessels that was not observed in sham‐treated eyes. Conclusions: In normal dogs, Bimatoprost SR was associated with a transient increase in EVP followed by a sustained decrease. Changes in EVP were accompanied by a sustained dilation of aqueous outflow vessels.